1995
DOI: 10.1002/mrd.1080410403
|View full text |Cite
|
Sign up to set email alerts
|

Murine polo like kinase 1 gene is expressed in meiotic testicular germ cells and oocytes

Abstract: To identify key molecules that regulate germ cell proliferation and differentiation, we have attempted to isolate protein kinase genes preferentially expressed in germ line cells. One such cDNA cloned from murine embryonic germ(EG) cells encodes a nonreceptor type serine/threonine kinase and is predominantly expressed in the testis, ovary, and spleen of adult mouse. The nucleotide sequence of the entire coding regions shows that this clone, designated Plk1(polo like kinase 1), is identical with STPK13 previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…An intriguing observation to emerge from this study is that the cells most sensitive to ME or MAA are the spermatocytes entering diplotene and the first meiotic division (stages XIII and XIV). A polo-like kinase-1 gene has been shown to be specifically expressed in the diplotene and diakinesis stages of meiotic prophase (34,35). Like the Drosophila polo-like kinase, the Plk-1 enzyme is believed to play an important role in meiosis, with an involvement in the regulation of microtubule organization and consequent spindle formation.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing observation to emerge from this study is that the cells most sensitive to ME or MAA are the spermatocytes entering diplotene and the first meiotic division (stages XIII and XIV). A polo-like kinase-1 gene has been shown to be specifically expressed in the diplotene and diakinesis stages of meiotic prophase (34,35). Like the Drosophila polo-like kinase, the Plk-1 enzyme is believed to play an important role in meiosis, with an involvement in the regulation of microtubule organization and consequent spindle formation.…”
Section: Discussionmentioning
confidence: 99%
“…A mammalian homolog of CDC5 is induced specifically during spermatogenesis (44). Two genes that are predicted to encode F-box proteins (45), YDR219 and YLR368, were induced midway through sporulation, raising the intriguing possibility that an SCF-like ubiquitin-conjugating complex may be necessary for progression through meiosis.…”
Section: Proposed Roles For Genes Induced During Sporulationmentioning
confidence: 99%
“…Plk1 is expressed at the highest levels in tissues with actively proliferating cell populations; for example, the placenta (Golsteyn et al, 1994;Hamanaka et al, 1994;Holtrich et al, 1994;Takai et al, 1999;Yoshimatsu et al, 1999;Wolf et al, 2000), spleen (Clay et al, 1993;Lake and Jelinek, 1993;Golsteyn et al, 1994), ovary (Lake and Jelinek, 1993;Golsteyn et al, 1994;Hamanaka et al, 1994;Matsubara et al, 1995;Takai et al, 1999), and testis (Lake and Jelinek, 1993;Golsteyn et al, 1994;Matsubara et al, 1995;Syed and Hecht, 1998). Indeed, Northern blot hybridization experiments have shown that Plk1 transcripts are either undetectable or present at very low levels in most other adult tissues, including the liver, kidney, brain, thymus, intestine, lung, pancreas, heart, stomach, and skin (Clay et al, 1993;Lake and Jelinek, 1993;Golsteyn et al, 1994;Hamanaka et al, 1994;Holtrich et al, 1994;Georgescu et al, 1997;Wolf et al, 2000).…”
Section: Normal Adult Tissues and Tumor Specimensmentioning
confidence: 99%